Novel BODIPY Dyes with a Meso-Benzoxadiazole Substituent: Synthesis, Photophysical Studies, and Cytotoxic Activity Under Normoxic and Hypoxic Conditions - Weronika Porolnik; Natalia Karpinska; Marek Murias; Jaroslaw Piskorz; Malgorzata Kucinska (Biomedicines)
Background/Objectives: Novel boron dipyrromethene derivatives with a heterocyclic, benzoxadiazole substituent were obtained as potential candidates for the photodynamic therapy (PDT) of cancers. Photochemical properties (e.g., singlet oxygen generation quantum yields (ΦΔ), absorption, and emission spectra) and cytotoxic activity studies in normoxic and hypoxic conditions were performed to verify the potential of novel BODIPYs as photosensitizers for PDT. Methods: Obtained dyes were characterized using mass spectrometry and various NMR techniques. The relative method with Rose Bengal as a reference and 1,3-diphenylisobenzofuran as a singlet oxygen quencher was used to determine ΦΔ values. The in vitro studies were conducted on human ovarian carcinoma (A2780) and human breast adenocarcinoma (MDA-MB-231) cells. Results: Photochemical studies showed that the presence of benzoxadiazole moiety only slightly affected the localization of the absorption maxima but resulted in fluorescence quenching compared with meso-phenyl-substituted analogs. In addition, brominated and iodinated analogs revealed a high ability to generate singlet oxygen. Anticancer studies showed high light-induced cytotoxicity of BODIPYs containing heavy atoms with very low IC50 values in the 3.5–10.3 nM range. Further experiments revealed that both compounds also demonstrated phototoxic activity under hypoxic conditions. The most potent cytotoxic effect in these conditions was observed in the iodinated BODIPY analog with IC50 values of about 0.3 and 0.4 μM for A2780 and MDA-MB-231 cells, respectively. Conclusions: The results of this study highlighted the advantages and some potential drawbacks of BODIPY compounds with heavy atoms and benzoxadiazole moiety as a useful scaffold in medicinal chemistry for designing new photosensitizers.